Effect of Combined Oral Contraceptive Pill on FVC, FEV1 and FEV1/FVC% - Islam, Farhana; Jahan, Nasim; Sultana, Nayma (Journal of Bangladesh Society of Physiologist, 2015)
Background: Combined oral contraceptive pill (COCP) is the most commonly used contraceptive method in Bangladesh. This COCP may have some effects on different organs including lungs. Objective: To observe the effects of combined oral contraceptive pill (COCP) on FVC, FEV1 and FEV1/ FVC% in apparently healthy women receiving COCP. Methods: This cross sectional study was carried out in the Department of Physiology, Sir Salimullah Medical College (SSMC), Dhaka between July 2013 and June 2014. A total 30 apparently healthy young women, age ranged 20 to 30 years were included in this study who were combined oral contraceptive pill users (COCP-U) for at least 6 months. Thirty age and BMI matched combined oral contraceptive pill nonusers (COCP-NU) were taken as control. FVC, FEV1 and FEV1/FVC% of all the subjects were measured by digital spirometer. Statistical analysis was done by Independent sample t test. Results: FVC (p<0.001), FEV1 (p<0.001) were significantly higher whereas, FEV1/FVC% (p<0.05) was significantly lower in COCP-U than those of COCP-NU. Moreover, the mean serum estrogen (p<0.001) and progesterone (p<0.05) levels were also significantly higher in COCP-U in comparison to those of COCP-NU. Conclusion: From the result of this study it can be concluded that COCP have beneficial effects on some pulmonary function parameters. Bangladesh Soc Physiol. 2015, June; 10(1): 21-25